A Response to Eamon Duffy - Skinner, Simon (The journal of ecclesiastical history, 2012)
At the close of his epistolary protest at Ian Ker's contemptuous review of John Henry Newman in the Times Literary Supplement in 2002, Frank Turner remarked: ‘Ker's review raises the larger issue of whether modern British and European religious history will continue as an arena for professional research and critical analysis or succumb to the parochial constraints and contentions of denominational and intra-denominational discourse. Ian Ker has made his choice in the matter, and I have made mine.’1 My article in this Journal in October 2010, ‘History versus hagiography: the reception of Turner's Newman’, sought to demonstrate that professional research and critical analysis were altogether suffocated by the contentions of denominational discourse after that book's publication in 2002. The article was careful not in any simple way to legitimise Turner's conclusions – indeed, it set out schematically and at length the interpretative retorts which they invited – but rather his purpose and method. I concluded:What is at stake … in the fuss over Turner's Newman, is not the plausibility or otherwise of his interpretation. It far transcends that. What is at stake is the legitimacy and remit of historical inquiry itself, when confronted with a vocal interest group whose principles and prejudices are seldom acknowledged. The difference between the book and the great majority of its critics, therefore, is not between Catholicism and Protestantism, nor even religion and secularism, but between history itself and hagiography – a difference not of prejudice, but of methodology.2A great – though mortal – man once wrote, in the Tracts for the Times, no. 1, ‘Choose your side’.3 In his response to my article on ‘History versus hagiography’, it is at once enlightening and dispiriting to see Eamon Duffy choosing his.